Math, asked by Anonymous, 5 months ago

please solve this ?

Attachments:

Answers

Answered by OoExtrovertoO
2

ᴀɴꜱᴡᴇʀ :

ʟᴇᴛ ꜰ(x) = x² + 3x ˗ 10

= x2 + 5x ˗ 2x ˗ 10

= x(x + 5) ˗ 2(x + 5)

= (x ˗ 2) (x + 5)

ᴛᴏ ꜰɪɴᴅ ᴛʜᴇ ᴢᴇʀᴏᴇꜱ, ꜱᴇᴛ ꜰ(x) = 0, ᴛʜᴇɴ

ᴇɪᴛʜᴇʀ x ˗ 2 = 0 ᴏʀ x + 5 = 0

⇒ x = 2 ᴏʀ x = −5.

ꜱᴏ, ᴛʜᴇ ᴢᴇʀᴏᴇꜱ ᴏꜰ ꜰ(x) ᴀʀᴇ 2 ᴀɴᴅ −5.

ᴀɢᴀɪɴ,

ꜱᴜᴍ ᴏꜰ ᴢᴇʀᴏᴇꜱ = 2 + (-5) = -3 = (-3)/1

= -ʙ/ᴀ

= (-ᴄᴏᴇꜰꜰɪᴄɪᴇɴᴛ ᴏꜰ x)/(ᴄᴏꜰꜰɪᴄɪᴇɴᴛ ᴏꜰ x²)

ᴘʀᴏᴅᴜᴄᴛ ᴏꜰ ᴢᴇʀᴏᴇꜱ = (2)(-5) = -10 = (-10)/1

= ᴄ/ᴀ

= ᴄᴏɴꜱᴛᴀɴᴛ ᴛᴇʀᴍ / ᴄᴏᴇꜰꜰɪᴄɪᴇɴᴛ ᴏꜰ x²

Similar questions